(untitled) (Journal of University of Babylon for Engineering Sciences, 2019)
In this study, the effect of (1%, 2%, 3%, 4% weight fraction) waste silica gel reinforced with (3% weight fraction) carbon fiber into unsaturated polyester resin was investigated on the tensile properties, impact strength and shore D hardness. These samples of polymeric composite materials were manufactured by (Hand-lay-up) method. The average particle size of the silica gel was (5.3 to 136.4 µm). The mechanical properties were analyzed using SPSS one way analysis of variance to determine which weight fraction has more influence on mechanical properties where statistical significance was set at P ≤ 0.05. Results showed that the highest mean values (164 ± 4.000 MPa), (7.367 ± .2517GPa) and (83.600 ± .2590) for tensile strength, elasticity modulus and hardness shore D respectively were recorded in sample (UP+3% C.F+4%Silica gel), while the highest mean values of elongation percentage (3.200 ± .2100), (2.700 ± .2100 ),(2.233 ± .1528) were recorded in samples (UP, UP+3% C.F, UP+3% C.F+1% silica gel) respectively, also highest mean values (10.9667±.07638) of impact strength was recorded in sample (UP+3% C.F+3% silica gel). The results of SPSS show that when (P) values less than (0.05) a significant effect of the filler material on the mechanical properties will be.